Psychosocial support in war areas using Community-Based Rehabilitation Strategy - Kocijan-Hercigonja, Dubravka (Array, 1997)
Wars and disasters call for new strategies to meet the increased needs of psychosocial support in the affected communities. There are great numbers of people having psycho-traumas, living in insecurity with problems of adaption to a new environment, sometimes being refused help and havig no trust in the helpers. In Crotatia, a community-based rahabilitation (CBR) strategy was developed to manage these problems, both for the physically injured and those with a need for psychosocial support. This letter will focus on the need for psycho-social support, with special emphasis on children and underline the usefullness of a CBR strategy in a war situation.